On the regularity of the stochastic heat equation on polygonal domains in R2 - Cioica-Licht, Petru A.; Kim, Kyeong Hun; Lee, Kijung (Journal of Differential Equations, 2019)
We establish existence, uniqueness and higher order weighted Lp-Sobolev regularity for the stochastic heat equation with zero Dirichlet boundary condition on angular domains and on polygonal domains in R2. We use a system of mixed weights consisting of appropriate powers of the distance to the vertexes and of the distance to the boundary to measure the regularity with respect to the space variable. In this way we can capture the influence of both main sources for singularities: the incompatibility between noise and boundary condition on the one hand and the singularities of the boundary on the other hand. The range of admissible powers of the distance to the vertexes is described in terms of the maximal interior angle and is sharp.
Keywords: Angular domain; Corner singularity; Polygonal domain; Stochastic heat equation; Stochastic partial differential equation; Weighted Lp-estimate